1998
DOI: 10.1039/a807680d
|View full text |Cite
|
Sign up to set email alerts
|

Surface and structural characterization of CexZr1-xO2 CEZIRENCAT mixed oxides as potential three-way catalyst promoters

Abstract: International audienceThe textural and structural properties of high specific surface area (HS) CexZr1-xO2 mixed oxides (CeZrMO) and their modification upon thermal aging have been investigated. Results from BET area determination and complete porosity analysis, as well as high-resolution electron microscopy, XRD, Raman and FTIR spectroscopies are presented. Some relationships between the molar composition of the binary systems and their textural and structural properties are presented. In addition, it has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
132
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(149 citation statements)
references
References 20 publications
17
132
0
Order By: Relevance
“…The slight shift to the right of the main (111) peak indicates a decrease of the lattice parameter due to Zr incorporation. The shift provides evidence of the formation of a solid solution that has been associated with superior catalytic properties by Colon et al (1998). Formation of a separate ZrO 2 phase is thought to be undesirable for a desulfurization sorbent.…”
Section: Xrd and Tem Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight shift to the right of the main (111) peak indicates a decrease of the lattice parameter due to Zr incorporation. The shift provides evidence of the formation of a solid solution that has been associated with superior catalytic properties by Colon et al (1998). Formation of a separate ZrO 2 phase is thought to be undesirable for a desulfurization sorbent.…”
Section: Xrd and Tem Characterizationmentioning
confidence: 99%
“…Colon et al (1998) state that the addition of ZrO 2 enhances the oxygen mobility within the crystal and improves the catalyst thermal stability at 1000 o C. Zamar et al (1995) Hori et al (1998) report an increase in reversibly stored oxygen by a factor of 1.7-2.5 for phase separated CeO 2 -ZrO 2 compared to CeO 2 alone, and by a factor 0f 3 to 5 for solid solutions of CeO 2 -ZrO 2 . The optimum Zr concentration was 25 mol%, but performance was relatively insensitive to Zr loading between 15 mol% and 50 mol%.…”
Section: Ceria-zirconia Catalyst Researchmentioning
confidence: 99%
“…Even without reduction, the solid solutions appear to evolve with high temperature aging. For example it has been reported that partial demixing of the solution occurs across the composition range upon aging at 1473 K and that new phases of approximate composition Ce 0.8 Zr 0.2 O 2 and Ce 0.12 Zr 0.88 O 2 form, although surface enrichment of neither of the elements is observed [58].…”
Section: Ceria and Mixed Metal Cerium Oxidesmentioning
confidence: 99%
“…The slight shift to the right of the main (111) peak indicates a decrease of the lattice parameter due to Zr incorporation. The shift provides evidence of the formation of a solid solution, that has been associated with superior catalytic properties Colon et al (1998). Formation of a separate ZrO 2 phase is undesirable from a catalytic perspective.…”
Section: Xrd and Tem Characterizationmentioning
confidence: 99%